Training and Mentoring on How to Provide Education Through the PERMATA Video "Mastectomy Care for Prosperous Patients" for Nurses (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Breast cancer following mastectomy has complex physical, psychological, and social impacts, including pain, risk of lymphedema, body image issues, and decreased self-acceptance. At the Kujangsari Community Health Center in Bandung City, post-mastectomy education services are still limited, generally delivered verbally without audiovisual support. This results in poor patient understanding of post-operative care. This community service activity aims to: (1) improve nurses' competence in providing video education to post-mastectomy patients, (2) improve patients' understanding and ability in self-care, (3) develop video-based education modules according to local needs, and (4) evaluate the effectiveness of interventions from the perspective of nurses and patients. The activity design included training, mentoring, and implementation of video education for community health center nurses over six months. The stages included preparation, training, field implementation, and evaluation. Instruments included a nurse knowledge questionnaire, a self-efficacy scale, an educational skills observation checklist, and a patient satisfaction questionnaire. Analysis was conducted quantitatively (pre-post difference test) and qualitatively (thematic interviews). Results showed a significant increase in nurses' knowledge and self-efficacy after training (mean increase 35%, p80%), particularly regarding the clarity of information and understanding of lymphedema prevention and arm mobilization. The main challenges encountered were limited technical resources, differences in patient educational backgrounds, and limited service time. A video-based educational program improves nurse capacity and patient understanding after mastectomy. This intervention is recommended for integration into routine community health center services, with support from facilities, ongoing training, and simple media alternatives to reach all patients.